Residents' attitudes toward tourism development in Socotra Island, Yemen - Mohd Nor, N.; Abdulqader, H.; Kasim, Azilah (2014)
Tourism industry has always been considered as a strategy to develop local community, economically and socially. However, tourism development requires participation and support from the local community to be sustained.It is perhaps the greatest challenge to the national government to get involvement, participation, support and acceptance from the local people, particularly in a conservative Islamic country such as Yemen.In Yemen, for instance, it is a challenge for the destination government to have a sustainable tourism development when Islamic values, culture, and the tribal conventions are in contrast to the Western tourists‘ practices.This paper discusses the residents‘ attitudes toward tourism development in a conservative community of Socotra Island in Yemen by looking at the influence of Islamic values on the residents‘ attitudes toward tourism development.Data was collected using qualitative method.Semi-structured interviews were conducted with 20 local people including local leaders to assess their attitudes toward tourism development in Socotra Island, Yemen.The results show that the residents‘ Islamic values influence the residents‘ attitudes toward tourism development in a conservative community of Socotra Island.The findings also indicate several factors that contribute to the residents‘ negative attitudes toward tourism development.This study extends the literature on residents‘ attitudes toward tourism by highlighting Yemeni Islamic values as a new variable in understanding community perceptions and attitudes toward tourism development.By understanding the locals‘ attitudes toward tourism, policy makers can better address the issues relating to tourism development in their countries.As a result, a sustainable tourism development is possible to be achieved.